Semiotic Analysis on Head Nod Ijab Qabûl of Deaf Groom in Islamic Marriage Law - Bustomi; Fauzan (INKLUSI, 2023)
This article aims to analyze the semantic side of a deaf wedding contract which interprets the contract with a nod of the head as the sign language. This qualitative research uses a phenomenological approach that reveals the experiences of three people in Bengkulu in 2021. In this case, the phenomenon in question is a nod of the head as an ijab qabûl. This study is interpreted by Charles Sanders Peirce's semiotic theory, which states that a sign is something used by an icon through an object so that it can function as a meaning for the interpretant. The analysis concluded that Deaf who nodded their heads as the qabûl words meant approval. Looking at Muslim scholar's opinions, especially as-Syarqâwi and al-Malibari, if the head nod means acceptance like such a phenomenon, the marriage contract of the Deaf is considered valid in Islamic law because the essence of qabûl is receiving an offer from the guardian of the bride. Artikel ini bertujuan untuk menganalisis sisi semantik akad pernikahan Tuli yang mengucapkan akadnya dengan anggukan kepala sebagai bahasa isyaratnya. Penelitian ini merupakan penelitian kualitatif yang menggunakan pendekatan fenomenologi yang mengungkap pengalaman kejadian ijab qabûl yang dilakukan oleh tiga orang Tuli di kota Bengkulu pada tahun 2021. Dalam hal ini, fenomena yang dimaksud adalah anggukan kepala sebagai ijab qabûl. Kajian ini dianalisis dengan teori semiotik Charless Sanders Peirce yang menyatakan bahwa tanda adalah sesuatu yang digunakan oleh suatu ikon melalui suatu objek sehingga dapat berfungsi sebagai pemaknaan bagi interpretan. Hasil analisis penelitian ini menyimpulkan bahwa Tuli yang menganggukkan kepalanya sebagai kata qabûl bermakna persetujuan. Sejalan dengan pendapat ulama fikih, terutama menurut as-Syarqâwi dan al-Malibari, perkawinan Tuli yang demikian dianggap sah dalam hukum Islam karena hakikat qabûl adalah mendapat izin dari wali pengantin perempuan.